Biotechnological approaches for improved disease resistance in soybean and wheat - Brungardt, Jordan J. (Kansas State University, 2020)
Increasing food production is required for the ever-increasing population. Reducing crop losses due to plant pathogens is a viable method of increasing this production. An estimated 12.5% of crop productivity is lost each year to plant pathogens. Here we explore two methods that utilize biotechnology for increasing resistance of common bread wheat (Triticum aestivum L.) to fungal pathogens, and soybean (Glycine max (L.) Merr.) to soybean cyst nematode (SCN; Heterodera glycines Ichinohe). Fungi are responsible for the largest amount of yield loss among plant pathogens. We have introduced six antifungal peptides (zeamatin, drosomycin, juruin, ARACIN, Ace-AMP1, and a wasabi gamma-thionin) into wheat via particle bombardment as single transgene lines along with a glufosinate resistance marker (BAR). Coding sequences (CDSs) were constitutively expressed via the pAHC17 plasmid. Lines expressing these genes were challenged with the ascomycete fungal pathogens Pyrenophora tritici-repentis, and Fusarium graminearum; as well as the basidiomycete fungal pathogen Tilletia laevis. Despite high levels of expression compared to housekeeping genes, these transgenes did not show enhanced resistance to these fungal pathogens. Zeamatin, drosomycin, and juruin CDSs were also subcloned into the soybean-optimized constitutive expression vector pGmubi. The other focus of this work looks at reducing reproductive success of SCN in the SCN/soybean pathosystem by exploiting SCN sex pheromones. SCN males have been shown to be attracted to females by several organic compounds, namely vanillic acid (VA). Here we engineer a pathway to produce VA in soybean in an attempt to mask females from males, thus lowering their reproductive success. Because of the long regeneration time required to recover transgenic soybean from particle bombardment of calli, preliminary work was conducted to show proof-of-concept. To check for inhibition of VA on soybean at SCN working concentrations, pouch bioassays were performed on 13-day old soybean seedlings. Root length of these seedlings was not inhibited by VA. Greenhouse experiments were conducted where susceptible soybean were challenged with SCN in the presence of different concentrations of exogenously applied VA. These assays did not show a reduction in cyst or egg numbers on soybean roots. A 3 dehydroshikimate dehydratase (3DSD) from Podospora anserina and a catechol o-methyltransferase (COMT) from Nicotiana tubacum were chosen for converting the shikimate pathway compound 3-dehydroshikimic acid into VA in planta. A Petunia x hybrida chloroplast targeting sequence fusion of these CDSs were subcloned into the pGmubi vector. These plasmids were introduced into soybean via particle bombardment either co-bombarded with the hygromycin resistance conferring plasmid pHyg, or tri-bombarded. Two greenhouse experiments were performed where T₁ soybean expressing 3DSD, COMT, and 3DSD+COMT were challenged with SCN. These plants did not show a reduction in numbers of cysts harvested from roots. More work needs to be done to dismiss this concept by doing larger greenhouse experiments with T₂ seed and plants expressing transgenes need to be characterized for production of VA. These observations indicate that VA may not act as a sex pheromone for SCN and needs to be investigated further.
Keywords: Wheat; Soybean; Biotechnology; Phytopathogenic fungi; Soybean cyst nematode; Antimicrobial peptides